Revisiting Wolbachia detections: Old and new issues in Aedes aegypti mosquitoes and other insects - Perran A. Ross; Ary A. Hoffmann (Ecology and Evolution, 2024)
Abstract Wolbachia continue to be reported in species previously thought to lack them, particularly Aedes aegypti mosquitoes. The presence of Wolbachia in this arbovirus vector is considered important because releases of mosquitoes with transinfected Wolbachia are being used around the world to suppress pathogen transmission and these efforts depend on a lack of Wolbachia in natural populations of this species. We previously assessed papers reporting Wolbachia in natural populations of Ae. aegypti and found little evidence that seemed convincing. However, since our review, more and more papers are emerging on Wolbachia detections in this species. Our purpose here is to evaluate these papers within the context of criteria we previously established but also new criteria that include the absence of releases of transinfections within the local areas being sampled which has contaminated natural populations in at least one case where novel detections have been reported. We also address the broader issue of Wolbachia detection in other insects where similar issues may arise which can affect overall estimates of this endosymbiont more generally. We note continuing shortcomings in papers purporting to find natural Wolbachia in Ae. aegypti which are applicable to other insects as well.